2016
DOI: 10.18632/oncotarget.10548
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis in tumorigenesis, activation of anti-tumor immunity, and cancer therapy

Abstract: While the mechanisms underlying apoptosis and autophagy have been well characterized over recent decades, another regulated cell death event, necroptosis, remains poorly understood. Elucidating the signaling networks involved in the regulation of necroptosis may allow this form of regulated cell death to be exploited for diagnosis and treatment of cancer, and will contribute to the understanding of the complex tumor microenvironment. In this review, we have summarized the mechanisms and regulation of necroptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 265 publications
(217 reference statements)
1
46
0
1
Order By: Relevance
“…Our analysis of apoptotic pharmacodynamic biomarkers revealed the absence of apoptosis-associated changes in cleaved caspase 3 or Mcl-1 levels following nilotinib-paclitaxel combination treatment in MDA-MB-468 xenografts, suggesting that an alternative mechanism of cell death may be responsible for the antitumor activity of this combination. Paclitaxel has previously been shown to induce both apoptosis and necrosis in a cell-cycle stage–specific manner (49), and a number of kinase inhibitors are known to induce necrosis (50), suggesting a potential role for nilotinib in shifting the apoptotic-necroptotic balance in paclitaxel-induced cell death. Regardless, the impressive in vitro activity and in vivo efficacy of this combination have motivated phase 1 evaluation of this drug pair (clinicaltrials.gov identifier: NCT02379416).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of apoptotic pharmacodynamic biomarkers revealed the absence of apoptosis-associated changes in cleaved caspase 3 or Mcl-1 levels following nilotinib-paclitaxel combination treatment in MDA-MB-468 xenografts, suggesting that an alternative mechanism of cell death may be responsible for the antitumor activity of this combination. Paclitaxel has previously been shown to induce both apoptosis and necrosis in a cell-cycle stage–specific manner (49), and a number of kinase inhibitors are known to induce necrosis (50), suggesting a potential role for nilotinib in shifting the apoptotic-necroptotic balance in paclitaxel-induced cell death. Regardless, the impressive in vitro activity and in vivo efficacy of this combination have motivated phase 1 evaluation of this drug pair (clinicaltrials.gov identifier: NCT02379416).…”
Section: Discussionmentioning
confidence: 99%
“…Defects in cancer cell death are the most frequent causes of therapeutic resistance, and thus exploring cancer cell death might inform development of strategies to overcome therapeutic resistance (4). Apoptosis is type-I Programmed cell death (PCD) that is morphologically characterized by cell shrinkage, chromatin condensation, nuclear fragmentation and formation of apoptotic bodies (5).…”
Section: Introductionmentioning
confidence: 99%
“…Necrosis has for a long time been considered an accidental mode of cell death. However, it was recently reported that a form of cell death morphologically classifi ed as necrosis (termed necroptosis) could also be regulated in a programmed manner via defi ned signal transduction pathways (4). Tumor necrosis factor (TNF) receptor 1 triggers a signaling reaction that culminates in binding of receptor interacting protein kinase 3 (RIPK3) with its upstream activator RIPK1.…”
Section: Introductionmentioning
confidence: 99%
“…MLKL was recently identified as a key effector molecule of necroptosis. It is phosphorylated by RIPK3 to form an oligomeric structure that translocates to the plasma membrane to disrupt membrane integrity and this can be used as a biochemical signature for necroptosis [19]. Studies have demonstrated that low MLKL expression indicated poor prognosis in colon cancer [20], ovarian cancer [21], and gastric cancer [22], indicating that MLKL might serve as a candidate tumor suppressor and a potential prognostic biomarker for various types of cancers.…”
Section: Discussionmentioning
confidence: 99%